Stedelike ontwikkeling in die Noordoos-Vrystaat : 'n sentraleplekstudie - Van Zyl, J. A.(Jacobus Adriaan) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (D. Phil.) -- Universiteit van Stellenbosch, 1968.